VIBRATION OF A FLOATING ICE SHEET. - Nevel,Donald E. (1970)
The solution for the vibration of an elastic plate floating on water is developed. The water is assumed to be incompressible and to have irrotational flow. In free vibration upon release of the plate, the maximum negative rebound of the deflection is 25%. For forced vibration, the steady state part of the solution shows that there is a frequency at which the deflection is a maximum. The stresses become a maximum at a frequency higher than the one for deflection. These critical frequencies depend upon the plate's characteristic length and the depth of the water. For most situations the critical frequency for stress is less than 0.2 cycle per second. At this critical frequency the stresses are amplified over the static case by a factor less than 10%. (Author)